EFFECT OF PRUNING INTENSITY ON THE PRODUCTION OF Pinus elliottii Engelm., IN PIRATINI, RS - Hoppe, Juarez Martins (2003)
The effect of the pruning intensity on the production of Pinus elliottii Engelm. in Piratini, RS, was studied in a randomized block design with four treatments and four replications. The treatments were: T1 - control, without pruning; T2 - pruning of 40% of the total height; T3 - pruning of 60% of the total height; T4 - pruning of 80% of the total height. It was observed that the diameter and wood volume were affected by the pruning intensity of the 13 year old stand. It is concluded that pruning intensities below 40% of the total height should be employed because of the lower production loss, and increment in diameter and quality of the wood.